PERSEPSI, PENYAJIAN DAN PENGUNGKAPAN DANA NON HALAL PADA BAZNAS DAN PKPU KABUPATEN LUMAJANG (UIN Sunan Kudus, 2014)
BAZNAS and PKPU are zakat organization wich is belive by muzakki.in theprocess of collecting zakat which is held by BAZNAS and PKPU. They havesome bank accounts, not only in the syariah bank but also in the conventionalbank. It purpose to be easier in the acceptence of zakat. From some sources,specially in the transfer system through conventional bank acccount.Whenthe acceptence by the conventional bank account, there is another resources.They are clearing account and rate of conventional bank but it is forbiden byIslamic law.BAZNAS and PKPUare difficultto those funds. The arrangementof financial report of BAZNAS and PKPU have not been appropriate to PSAKNo. 109, because there is limitted human resource.BAZNAS and PKPU haveperception which is different about unpermitted fund in the financial reporseperately, but they have not presented it.